IMPLEMENTATION OF PANCASILA VALUES AS THE BASIS OF THE STATE IN THE FORMATION OF LEGISLATION AND REGULATIONS - Rahmansyah Fadlul Al Karim Rambe (LEX SOCIETAS: Journal of Law and Public Administration, 2024)
Pancasila as the foundation of the state has a fundamental role in shaping the legal system and legislation in Indonesia. The implementation of Pancasila values ​​in the formation of legislation aims to ensure that every legal product reflects the principles contained in Pancasila, namely Divinity, Humanity, Unity, Democracy, and Social Justice (Rambe, 2019). This study examines how Pancasila is applied in the legislative process, from policy formulation to enactment of laws, and how these values ​​become benchmarks in assessing the legitimacy and justice of law in Indonesia. The results of the study show that the implementation of Pancasila in the formation of legislation provides a strong moral and ethical foundation for every policy issued. The values ​​of Pancasila serve as a guideline to ensure that the laws made are able to reflect the aspirations of the diverse and just Indonesian people. However, in practice, challenges arise in maintaining consistency between the values ​​of Pancasila and the realization of policies that are responsive to social, political, and economic dynamics. In conclusion, although Pancasila has become the main foundation in the legal system, ongoing efforts are needed to improve the integration of these values ​​consistently in every stage of legal formation. Thus, the resulting laws and regulations can better reflect social justice and the aspirations of all Indonesian people, in accordance with the spirit of Pancasila as the foundation of the state